Numerical simulation of charged fullerene spectrum - Arutyunyan, Rafael; Obukhov, Yuri; Vabishchevich, Petr (Mathematical Modelling and Analysis, 2019)
The mathematical model of the ground state electron spectrum of a charged fullerene is constructed on the basis of the potential of a charged sphere and the spherically symmetric potential of a neutral fullerene, derived in a single-electron self-consistent ﬁeld model approach. The electron spectrum is deﬁned as the solution of the spectral problem for the one-dimensional Schrödinger equation. For the numerical solution of the spectral problem, piecewise-linear ﬁnite elements are used. The computational algorithm was tested on the analytical solution of the problem of the spectrum of the hydrogen atom. For solution of matrix spectral problems, a free library for solving spectral problems of SLEPc is used. The results of calculations of the electron spectrum of a charged fullerene C60 are presented.